Simulação do recobrimento de partículas em leito de jorro usando modelos de balanço populacional - Silva, Danylo de Oliveira (2006)
A dynamic simplified model based on population balances is used to calculate the population density function of a particles coating process in a spouted bed with a draft tube, considering an independent size growing. The model considers the bed composed by two constant size domains of perfect mixture, where occurs coating and drying of particles, with circulation among them. The model is made dimensionless, so that the independent variable related to the coating mass is equal to the dimensionless residence time in the coating domain. This way, the distribution functions can be treated as residence time distributions, defined for each domain. The model is formed by hyperbolic partial differential equations, being analytically solved by Laplace transform and Moments Method. The model parameters that define the coating and drying domains, the porosity profile at the fountain and the particles circulation rate are obtained through geometric relationships and CFD simulations. The experimental frequency distribution curves related to the soybean seeds coating with inoculant and micronutrients, for different operational conditions and at the final operation time were compared with the simulated ones by the model, showing a good agreement. The values of moments, averages and standard deviations, analytically calculated, are presented for the several simulated cases, allowing the evaluation of the coating uniformity. The representation by normal distributions was not appropriated at the simulated conditions. The effects of the coating suspension flow rate and of the coating domain size over the distributions are analyzed, allowing the identification of operational conditions which make possible larger coating uniformity.